Pengembangan E-Book pada Mata Kuliah Teknologi Sensor dan Kontrol Elektronik Otomotif - Hamdi Ramadhan; Irma Yulia Basri; Hasan Maksum; Rifdarmon Rifdarmon (TSAQOFAH, 2026)
The limited availability of teaching materials in the Automotive Sensor Technology and Electronic Control course is an obstacle in learning, because the lecture process is still dominated by presentation media and lecturers’ explanations, causing students to experience difficulties in understanding abstract and technical material. In addition, no digital teaching materials are yet available to support students’ independent learning. This study aims to produce an e-book that is valid and feasible for use as a learning medium in the Automotive Sensor Technology and Electronic Control course. This study used the Research and Development method with the 4D model, which includes the Define, Design, Develop, and Disseminate stages, but its implementation was limited to the Develop stage. The research subjects consisted of two validators from the Department of Automotive Engineering, Universitas Negeri Padang. Data were collected using a validation questionnaire covering the aspects of material, media, language, and instructional design, then analyzed descriptively and quantitatively through the calculation of the product validity percentage. The results showed that the developed e-book had a very high level of validity, with a material validation percentage of 89.29%, media validation of 96%, language validation of 91.74%, and instructional design validation of 89.33%. The conclusion of this study affirms that the e-book for the Automotive Sensor Technology and Electronic Control course is declared very valid and feasible for use as a learning medium. These findings imply the provision of digital teaching materials that can support independent learning and help students understand technical material on automotive sensors and electronic control.